Contrasting impacts of gold mining and oil palm expansion on ecosystem functioning in the Peruvian Amazon - Hebert Castillo; Juan Carlos Guerra; Fabio Sakaguchi; Deyvis Cano; Pablo Baldassini (Remote Sensing Applications: Society and Environment, 2026)

Oral selenium supplementation improves the reproductive performance of rams: A systematic review and meta-analysis - Alfonso Longinos Muñoz-Benitez; Rodolfo Vieyra-Alberto; Juan Hebert Hernandez-Medrano; José Luis Ponce Covarrubias; Erika Georgina Hernández-Rojas; David Alejandro Contreras Caro del Castillo; Juan Carlos Angeles-Hernandez (Small Ruminant Research, 2025)

Effect of canola oil supplementation level on total tract digestion, ruminal fermentation, and methane emissions of cows grazing Urochloa sp. supplemented with a fixed amount of concentrate - Jonathan Noe Avilés-Nieto; Claudia Cecilia Márquez-Mota; Juan Hebert Hernández-Medrano; Jacinto Efrén Ramírez-Bribiesca; Epigmenio Castillo-Gallegos; Alejandro Plascencia; Francisco Alejandro Castrejón-Pineda; Luis Corona (Tropical Animal Health and Production, 2023)
Four rumen-cannulated cows ( Bos taurus × Bos indicus , 657 ± 92 kg body weight, BW) in a rotational grazing ( Urochloa sp.) system were assigned to different canola oil (CO) inclusion levels, 0.0, 0.40, 0.80, and 1.2 g/kg according to shrunk body weight (SBW, BW adjusted for gastrointestinal filling) in a 4 × 4 Latin Square design to evaluate CO on the CH 4 emissions and dietary energy intake. CH 4 emissions were estimated using an infrared analyzer methodology ( Sniffer method). Grass intake and fecal production were estimated using Cr 2 O 3 as an external marker. CO supplementation increased (linear effect, P ≤ 0.05) total dry matter and gross energy intake with a linear increase ( P = 0.09) in neutral detergent fiber (NDF) intake. While digestible energy (Mcal/kg) linearly increased with increasing CO supplementation level (linear effect, P < 0.05), total tract digestion of organic matter, NDF, and CP was comparable ( P > 0.05) between levels. Maximal CO supplementation (1.2 g/kg SBW) significantly decreased total ruminal protozoa population, acetate:propionate ratio, and enteric methane production (g/kg DMI) by 9, 5.3, and 17.5%, respectively. This study showed that, for cows grazing tropical forages, CO can be supplemented up to 1.2 g/kg SBW (5.8% of the total diet) without negatively affecting intake and nutrient digestion while reducing ruminal fermentation efficiency and enteric methane emission (≤ 17.5%).

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (